Development and Validation of an Indonesian Version of the College Students' Adaptation Scale: A Dimensionality Analysis - Moch. Syihabudin Nuha; Henny Indreswari; Khairul Bariyyah (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Adaptation is a crucial ability that enables individuals to cope with new and unfamiliar environments. For college students, the ability to adapt during their first year is key to achieving academic success and maintaining psychological well-being. This study aims to develop and validate an assessment instrument to measure the adaptation levels of college students. The research adopts a development methodology using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. A questionnaire was constructed based on Baker and Siryk’s theory, encompassing four dimensions of adaptation: academic adaptation, social adaptation, personal-emotional adaptation, and attachment to institutions. The questionnaire items were designed using a Likert scale and validated through expert review and field testing. The initial data were collected from 30 respondents for validity and reliability analysis. Results indicate that the instrument achieves a Cronbach's Alpha reliability score of 0.760, which is classified as high, confirming its consistency in measuring adaptation. However, only 10 out of 44 items met the validity criteria with Pearson correlation values greater than 0.3. These items reflect critical aspects of academic motivation, social participation, psychological adjustment, and institutional engagement. The findings demonstrate that the developed instrument is valid and reliable, making it feasible for evaluating the adaptation levels of college students. Future research should refine the instrument further through exploratory and confirmatory factor analyses with larger sample sizes to improve item precision and generalizability. This instrument holds potential for use by university counselors to identify adaptation challenges in students and develop targeted interventions. Keywords: college student adaptation, instrument development, ADDIE model, student adjustment, validation study.